2001
DOI: 10.2144/01314pf01
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield, In Vitro Protein Expression Using a Continuous-Exchange, Coupled Transcription/Translation System

Abstract: The Rapid Translation System (RTS 500) (Roche Molecular Biochemicals) is a high-yield protein expression system that utilizes an enhanced E. coli lysate for an in vitro transcription/translation reaction. In contrast to conventional transcription/translation, this system allows protein expression to continue for more than 24 h. We demonstrated the utility of the RTS 500 by expressing different soluble and active proteins that generally pose problems in cell-based expression systems. We first expressed GFP-luna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…To avoid cytotoxicity or formation of inclusion bodies of expression proteins, the expression of reVVA2 I82E/L86K or reCTF in vitro was performed with a Rapid Translation System RTS 500, which utilizes an enhanced E. coli lysate for an in vitro transcription/translation reaction (22). Reactions were carried out at 28°C for 24 h and then the reaction mixtures were centrifuged at 20,000 ϫ g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid cytotoxicity or formation of inclusion bodies of expression proteins, the expression of reVVA2 I82E/L86K or reCTF in vitro was performed with a Rapid Translation System RTS 500, which utilizes an enhanced E. coli lysate for an in vitro transcription/translation reaction (22). Reactions were carried out at 28°C for 24 h and then the reaction mixtures were centrifuged at 20,000 ϫ g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, we utilized a complete E. coli system for in vitro synthesis of protein products and optimized this system for maximum yield and activity of products synthesized in a high throughput mode. A long-lasting, E. coli-based system has also been recently described by Roche (Martin et al 2001). It allows protein expression to continue for more than 24 h. However, this system requires the use of a costly apparatus and allows only a single protein to be synthesized at a time.…”
Section: Discussionmentioning
confidence: 99%
“…In the 0.05-µ l microreactor, the effectiveness of protein synthesis was 1.5 mg proinsulin per ml; the pellet accounted for only one fifth of the synthesized proinsulin. In the reactor from Roche [12], the yield of proinsulin was 1.8 mg/ml, out of which only 0.3 mg were in pellet. On the basis of these data, we concluded that an increase in the volume of reaction medium (the socalled translation system scaling) had no adverse effect on the amount and solubility of proinsulin synthesized (Fig.…”
Section: Preparative Synthesis Of Human Proinsulinmentioning
confidence: 99%